PENERAPAN PRINSIP-PRINSIP PERTANIAN BERKELANJUTAN PADA USAHATANI PADI SAWAH DI DESA CIALAM JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Wirasta, Nengah; Nalefo, La; Arif, La Ode Kasno (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
This study aims to determine the application of sustainable agriculture principles in paddy rice farming in Cialam Jaya village, Konda sub-district, South Konawe district. Informants were determined by snowball sampling with a total of 6 informants. The method in this study uses qualitative analysis, as for the analysis used in this study, namely: data reduction, data analysis and data interpretation. The results showed that the application of the principles of sustainable agriculture on wet-rice farming in the village was at the adaptation stage, but not yet fully sustainable. Farmers have implemented several principles such as crop diversification, integrated pest control, and the use of organic fertilizers, but still depend on the use of chemical fertilizers and pesticides. More intensive efforts are needed to improve the overall application of sustainable agriculture principles in order to achieve sustainability of food production, environmental protection and improvement of farmers' welfare.